Efficient Catalyst-Free Henry Reaction between Nitroalkanes and Aldehydes or Trifluoromethyl Ketones Promoted by Tap Water - Du, Zhi-Hong; Yuan, Meng; Tao, Bao-Xiu; Ding, Tie-Ying; Da, Chao-Shan (Synthesis, 2022)
The first examples of highly effective Henry reactions between nitroalkanes and aldehydes or trifluoromethyl ketones that proceed under catalyst-free and additive-free conditions, in a recyclable tap water medium, and at room temperature are reported. This process tolerates a broad range of aldehydes and trifluoromethyl ketones to give a series of β-nitro alcohol products in excellent yields. Such products are widely used in the syntheses of pharmaceutical intermediates and natural products. This protocol can be successfully scaled up to a 50-mmol scale without a reduction in yield. Tap water from different locations in China exhibited pH values ranging from 7.5 to 8.1, but the varying pH had no effect on the yield and the processes were successfully reproduced. Finally, the tap water was effectively recovered and reused without any postprocessing, even when the reaction substrates were different.
Keywords: tap water; green synthesis; catalyst free; Henry reaction; trifluoromethyl ketones